Information Communication Technology and Social Change - Sambasivan, K. (Journal of Information and Knowledge, 2002)
Due to the rapid development and diffusion of information communication technology in all walks of life, the entire human society is on the verge of a transition or transformation. The large scale of computerization in each and every activity, tremendous and rapid growth of electronic information, combined  with global access of information via telecommunication infrastructure etc. are some of the underlying factors of the present transformation process. For each and every user activity information is emerging as a valuable resource at all levels, such as education research and development, advancing the frontiers of knowledge, competitiveness in business and indust1),. economic and social development, improving the quality of day-to-day life etc. There is no doubt that information will occupy a center stage position governing human life in the coming century making a profound impact on social, economic and political activities of every society.